STRATEGI PEMASARAN SYARIAH DALAM MEMBANGUN LOYALITAS NASABAH PADA PERBANKAN SYARIAH - Vania Khairunisa Lubis (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the application of sharia marketing strategies implemented by Islamic banks in an effort to increase customer loyalty. The study uses a qualitative approach by reviewing various relevant literature sources in the form of books and scientific articles. The focus of the study is on marketing strategies that emphasize service quality and customer relationship management. The results of the study indicate that excellent service, the implementation of customer relationship management (CRM), and product innovation in accordance with sharia principles play an important role in building and maintaining customer loyalty. Compliance with sharia values, the provision of personalized services, and ongoing education about Islamic banking products have been proven to increase customer trust. In addition, the use of digital technology, such as online banking services, contributes to improving customer access and satisfaction. Despite facing a number of obstacles, such as a lack of awareness regarding the use of applications and limited internet access in some areas, this study concludes that effectively implemented sharia marketing strategies can strengthen the relationship between banks and customers and expand the market share of sharia banking in the national banking industry.